The sustainability status and the development strategy of collective cage-based beef cattle smallholder farming on Lombok Island: the dimension of disease incidence - Mashur Mashur; Hunaepi Hunaepi; Taufik Samsuri (IKIP Mataram, 2023)
The incidence of the disease is one of the problems faced by beef cattle farms in Lombok Island, West Nusa Tenggara Province in increasing the production and productivity of livestock. On smallholder livestock, beef cattle are maintained intensively using a collective cage group, making it easier to manage and promote them. This aim is to analyze the status of the sustainability of the development of beef cattle smallholder farming based on collective cages in Lombok Island from the dimension of disease incidence. The method used to determine the sustainability status is Multi-Dimensional Scaling (MDS) with the Rapid Appraisal Beef Cattle Diseases (RAPBCD) approach of 20 diseases as attributes. The sensitive attributes that affect the sustainability index and the effect of errors are determined based on the Leverage analysis and Monte Carlo test. The results of the sustainability analysis showed that the status of the dimensions of the disease incidence dimension was 56.38%. The analysis results of the 20 diseases as attributes studied, 9 diseases (diarrhea, scabies, flatulence, itching, demodec, pink eye, anthrax, reproductive, epizootic septimea) are sensitive attributes and need to be improved because they will affect increasing the value of the sustainability index. Determination of the key factors of sustainability is obtained by prospective analysis to determine the future strategy for the development of collective cage-based beef cattle smallholder farming. The conclusion is that the status of the sustainability of the development of collective cage-based beef cattle smallholder farming on Lombok Island from the dimension of disease incidence is in a fairly sustainable category with four recommended development strategies, namely: strategies to improve beef cattle health management; increasing access to information and livestock health technology; increasing the role of the government, businessmen, and other stakeholders and strengthening farmer institutions, farmer economic institutions.